Incorporation of a Glass to Enhance the Performance of Solar dryers in the El-Oued region (Algeria) - LAGGOUN ,Nadjet; ADAIKA, Djoumana (Université of eloued جامعة الوادي, 2025)
This study aims to enhance the performance of an indirect solar dryer (ISD) by integrating a glass cover (GC) and a tracking mechanism to maximize solar radiation absorption within the drying chamber. Two main experiments were conducted under real weather conditions in El Oued city, located in the Algerian Sahara during April and May 2025. The results revealed that the first experiment investigated the effect of the GC on the ISD’s thermal performance. The maximum temperature at the high levels of drying was obtained in the dryer with GC and a tracking mechanism. The values for the drying efficiency of the drying process were 34.01502% and 30.01502% for the processes with and without GC, respectively. The results indicate that ISD with GC showed shorter drying time than ISD without GC or open sun drying. The future challenges and recommendations on the selection, implementation and testing of the glass over and tracking mechanism for different solar dryers are also reported. تهدف هذه الدراسة إلى تحسين أداء مجفف شمسي ذو الماص المقلوب (ISD) من خلال دمج غطاء زجاجي (GC) وآلية تتبع لتعظيم امتصاص الإشعاع الشمسي داخل حجرة التجفيف . أجريت تجربتان رئيسيتان في ظل ظروف جوية حقيقية في مدينة الوادي الواقعة في الصحراء الجزائرية خلال شهري أبريل ومايو 2122 . كشفت النتائج أن التجربة الأولى بحثت في تأثير الغطاء زجاجي (GC) على الأداء الحراري لمجفف (ISD) . تم الحصول على أقصى درجة حرارة عند مستويات التجفيف العالية في المجفف باستخدام GC وآلية تتبع . كانت قيم كفاءة التجفيف لعملية التجفيف 30.10212 ٪ و 31.10212 ٪ للعمليات مع GC وبدونها على التوالي . تشير النتائج إلى أن ISD مع GC أظهر وقت تجفيف أقصر من ISD بدون GC أو التجفيف الشمسي المفتوح . كما تم الإبلاغ عن التحديات المستقبلية والتوصيات بشأن اختيار وتنفيذ واختبار الغطاء الزجاجي وآلية التتبع لمختلف المجففات الشمسية .
Radiation physics
Keywords: Indirect solar dyer; Glass Cover; tracking mechanism; Efficiency; جفف شمسي غير مباشر، غطاء زجاجي، آلية تتبع، كفاءة، أداء